Learning with the Mosiulika Mosijagai Method at SMKN 2 Palu, Post-Earthquake in Central Sulawesi - Nurhawaisyah Nurhawaisyah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Mosiulika Mosijagai is the Kaili Ledo language in the city of Palu, Central Sulawesi Province. Mosiulika means